Grain Boundary Segregation in Metals - Lejcek, Pavel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Grain boundaries are important structural components of polycrystalline materials used in the vast majority of technical applications. Because grain boundaries form a continuous network throughout such materials, their properties may limit their practical use. One of the serious phenomena which evoke these limitations is the grain boundary segregation of impurities. It results in the loss of grain boundary cohesion and consequently, in brittle fracture of the materials. The current book deals with fundamentals of grain boundary segregation in metallic materials and its relationship to the grain boundary structure, classification and other materials properties.
Grain Boundaries: Description, Structure and Thermodynamics -- Approaches to Study Grain Boundary Segregation -- Models of Equilibrium Grain Boundary Segregation -- Effect of Variables on Equilibrium Grain Boundary Segregation -- Principles of Non-equilibrium Segregation -- Grain Boundary Segregation and Related Phenomena.
Keywords: Industrial engineering; Engineering economy; Management information systems; Materials; Materials Science; Metallic Materials; Engineering Economics, Organization, Logistics, Marketing; Industrial and Production Engineering; Business Information Systems